Methylation assay in KMT2B-related dystonia: a novel diagnostic validation tool - Gleyson Francisco da Silva Carvalho; Claudio Melo de Gusmão; Beatriz Martins Wolff; Lucas Liro Vieira; Yanca Gasparini de Oliveira; Mariana Ribeiro Costa; Rafaela da Silva Mendes; Matheus Augusto Araujo Castro; Mayara T. Sakuma; Fernando Kok; Bekim Sadikovic; Leslie Domenici Kulikowski (Clinical Epigenetics)
Abstract Background/objectives KMT2B-related dystonia (DYT28, OMIM #617284) is a progressive neurological condition characterized by early onset movement disorders with autosomal dominant inheritance. In this study, we describe the use of a genome methylation episignature methodology to functionally validate two variants of uncertain significance (VUS) in the KMT2B gene. Methods Genome-wide methylation status was assessed using the EPIC methylation assay in peripheral blood samples from two subjects with early onset movement disorder and missense variants of uncertain significance in the KMT2B gene (p.Leu1720Phe and p.Tyr2515Cys). After QC and normalization steps, we compared the M values for all 144 probes, previously described as an EpiSign for KMT2B-related dystonia, between the two subjects and 14 controls individuals. Results The individual harboring the p.Tyr2515Cys variant exhibited a hypermethylation profile compatible with pathogenic/likely pathogenic variants in KMT2B, allowing for variant reclassification, conclusive genetic counseling, and patient stratification for deep brain stimulation. In contrast, the individual harboring the p.Leu1720Phe variant had a methylation status similar to controls, practically ruling out KMT2B-related dystonia. Conclusion Investigation of methylation status can be a powerful tool to determine pathogenicity when facing KMT2B variants of uncertain significance. Methylation results may optimize genetic counseling and positively impact patient care.